(Hi-)Stories of the Gulag: fiction and reality - Fischer von Weikersthal, Felicitas; Thaidigsmann, Karoline (Universitätsverlag Winter, 2016)
Cover -- Title Page -- Copyright -- Contents -- Introduction. Felicitas Fischer von Weikersthal, Karoline Thaidigsmann -- Galina IVANOVA, Competing Realities: Statistics, Memoirs and the History of the Gulag [Die Gulag-Statistiken im Spiegel von Archivmaterialien und Memoiren] -- Dan HEALEY, "Dramatological" Trauma in the Gulag. Malingering, Self-Inflicted Injuries and the Prisoner-Patient -- Friedrich GEIGER, Music in the Recollections of Political Gulag Prisoners -- Felicitas Fischer VON WEIKERSTHAL, Appearance and Reality. Nazi Germany and Gulag-Memoirs -- Manuela PUTZ, „Auf dem Weg nach vorne. Polithäftlinge sind wir". Politische Gefangenschaft, transnationale Netzwerke und Identitätskonstruktionen Andersdenkender in der Sowjetunion der 1960er bis 1980er Jahre -- Zuzanna BOGUMIŁ, The Solovetski Islands and Butovo as two "Russian Golgothas". New Martyrdom as a Means to Understand Soviet Repression -- Anne HARTMANN, Fiction and Reality: Literary Testimonies Between Document and Fictionalization Erschöpft und usurpiert. Plädoyer für ein erweitertes Konzept von Gulag-Literatur -- Andrea GULLOTTA, Gulag Poetry. An Almost Unexplored Field of Research -- Leona TOKER, Rereading Varlam Shalamov's Stories June and May. Four Kinds of Knowledge -- Alfred GALL, Disconcerting Concision. Laconism as Principle of Text Organization - Leo Lipski (Dzień i noc) and Lev Konson (Kratkie povesti) -- Łukasz Neca, Fiktive Wirklichkeiten - wirkliche Fiktionen. Gustaw Herling-Grudzinskis Inny swiat und Wlodzimierz Odojewskis Zabezpieczanie sladów -- Renate LACHMANN, Document or Fiction? Karlo Štajner and Danilo Kiš -- Karoline THAIDIGSMANN, Inventing the Gulag: Approaches in Contemporary Literature, Music and Film Visitors to the Gulag. Soviet Forced Labor in Contemporary Western Fiction for Adult and Young Readers.